1992
DOI: 10.1242/jeb.172.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a conserved 95–120 KDA subunit associated with and essential for activity of V-ATPases

Abstract: Vacuoles purified from Saccharomyces cerevisiae bearing the vph1-1 mutation had no detectable bafilomycin-sensitive ATPase activity or ATP-dependent proton pumping. Furthermore, the vacuolar H(+)-ATPase (V-ATPase) nucleotide binding subunits were no longer associated with vacuolar membranes yet were present at wild-type levels in yeast whole-cell extracts. The VPH1 gene was cloned by screening a lambda gt11 expression library with antibodies directed against a 95 kDa vacuolar integral membrane protein and inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The upregulation of these genes revealed the enhanced uptake of flu nanoagents by nematodes via the endocytic pathway. This result is in line with our previous discoveries, indicating that SPc can trigger clathrin-mediated endocytosis to facilitate the uptake of diverse exogenous materials. , Among the encoded proteins of energy-related genes, vATPA (V-type proton ATPase subunit A) is a multisubunit enzyme that hydrolyzes ATP and a membrane integral complex . The downregulation of the vATPA gene suggested that the flu nanoagent might adversely influence ATP generation compared to flu alone, which further disturbed the expression of other energy-related genes.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The upregulation of these genes revealed the enhanced uptake of flu nanoagents by nematodes via the endocytic pathway. This result is in line with our previous discoveries, indicating that SPc can trigger clathrin-mediated endocytosis to facilitate the uptake of diverse exogenous materials. , Among the encoded proteins of energy-related genes, vATPA (V-type proton ATPase subunit A) is a multisubunit enzyme that hydrolyzes ATP and a membrane integral complex . The downregulation of the vATPA gene suggested that the flu nanoagent might adversely influence ATP generation compared to flu alone, which further disturbed the expression of other energy-related genes.…”
Section: Resultssupporting
confidence: 90%
“…23,24 Among the encoded proteins of energy-related genes, vATPA (V-type proton ATPase subunit A) is a multisubunit enzyme that hydrolyzes ATP and a membrane integral complex. 71 The downregulation of the vATPA gene suggested that the flu nanoagent might adversely influence ATP generation compared to flu alone, which further disturbed the expression of other energy-related genes. For instance, the PIF1 (ATP-dependent DNA helicase PIF1) gene, which maintains both mitochondrial and nuclear genome stability, and the Ath (ATP-dependent RNA helicase DHX33) gene, which coordinates germline stem cell differentiation, were upregulated.…”
Section: Improved Bioactivity Of Flu Nanoagents By Disturbing the Exp...mentioning
confidence: 99%